Synergistic Effect Between Online Broadcast Media and Interactive Media on Purchase Intention - Gao, Yin; Zhao, Lin (Frontiers in Psychology, 2021)
Using online broadcast media and interactive media simultaneously is becoming increasingly important for marketers. The current paper describes three studies that were conducted to explain the mechanism inherent in the synergy effect. We ran Study 1 to test the synergy effect of online broadcast media and interactive media on purchase behavior. We conducted a 2 (synergy group vs. non-synergy group) experiment to test the differences between groups. Study 2 was a 2 (interference term vs. no interference term) × 2 (synergistic group vs. non-synergistic group) experiment to test whether the interaction between online broadcast media and interactive media is a necessary condition for the synergistic effect. Finally, Study 3 was conducted to test the difference in the level of information processing between online broadcast media and interactive media as a necessary condition for the synergistic effect. We designed a 2 (questioning vs. not questioning) × 2 (synergy group vs. non-synergy group) experiment to examine the difference between groups. The results show that online broadcast media and interactive media have a synergy effect on consumer purchase intention and memory. Study 1 shows that participants in the synergistic group had a higher purchase intention than participants in the non-synergistic group. Study 2 revealed a significant cognition interaction effect on product memory between online broadcast media and interactive media. Finally, the difference in information processing level between broadcast media and interactive media had a significant synergy effect on product memory in Study 3.